Business model for content websites and blogs profiting from contracts with online advertising service providers : the case of www.thebusinesszoom.com - Müller, João Diogo (2015)
The last decades have been marked by a huge growth and transformation of online tendencies. This area is full of globally provided contents and new opportunities to be explored by entrepreneurs. Online advertising plays a big role in this sector while giving many publishers the opportunity to get revenue from their websites by reproducing ad blocks, which in fact nowadays internet surfers are very used to seeing while searching online. The goals of this dissertation go exactly in the direction of understanding the business model’s viability and processes that should be considered by these website owners and bloggers when publishing other companies’ ads or products through advertising service providers such as Google AdSense and being monetized with compensation models such as the CPC (cost per click) and CPM (cost per mile). As part of this research the website www.thebusinesszoom.com was used as an extension to this approach, providing experiences, statistics and results from a real website using online advertising service providers to get monetized. Apart from this resource, some opinions from experts in this field and website owners were analyzed in order to understand and highlight the main parameters and important mechanisms used to attract more users and consequently make this business more profitable by leveraging the visibility of the advertising blocks. As a conclusion, this dissertation brought some recommendations for bloggers and website owners, focusing on the key procedures that are essential to improving the results of this business model.